2017
DOI: 10.1002/ajmg.b.32596
|View full text |Cite
|
Sign up to set email alerts
|

A functional polymorphism of the OXTR gene is associated with autistic traits in Caucasian and Asian populations

Abstract: There is increasing evidence for associations between polymorphisms of the oxytocin receptor (OXTR) gene and autism spectrum disorder, but to date no study has established links with autistic traits in healthy subjects and potential cultural differences. The present research firstly investigated associations between three widely studied OXTR SNPs and autistic and empathic traits (rs53576 (G/A); rs2254298 (G/A); rs2268498 (T/C)) in two independent studies on male and female Caucasian (n = 537) and Chinese stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 39 publications
5
48
0
Order By: Relevance
“…For OXTR genotyping subjects provided buccal swaps on the 1 st day for analysis of OXTR rs2254298, rs53576 SNPs (see SI and [28]).…”
Section: Methodsmentioning
confidence: 99%
“…For OXTR genotyping subjects provided buccal swaps on the 1 st day for analysis of OXTR rs2254298, rs53576 SNPs (see SI and [28]).…”
Section: Methodsmentioning
confidence: 99%
“…Although previous findings on interaction effects involving self-other condition, valence and treatment during the subsequent recognition memory test in the paradigm could not be replicated [4], including OXTR genotype as an additional factor in the analysis revealed that intranasal OXT decreased memory performance for negatively valenced words during the stranger condition specifically for rs2268498 T homozygotes but not C carriers. Previous studies reported that the rs2268498 T homozygotes had higher scores of empathic concern relative to those carrying a C allele [20] and that T-allele variant associates with better social perception [48] and lower trait autism scores [21]. On the other hand, C carriers have a greater association with higher trait autism [21].…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies reported that the rs2268498 T homozygotes had higher scores of empathic concern relative to those carrying a C allele [20] and that T-allele variant associates with better social perception [48] and lower trait autism scores [21]. On the other hand, C carriers have a greater association with higher trait autism [21].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations